2014
DOI: 10.1155/2014/894095
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Corneal Collagen Cross-Linking in Pediatric Patients: Two-Year Follow-Up Results

Abstract: Purpose. To evaluate the effectiveness and safety of accelerated corneal collagen cross-linking (ACXL) in patients below 14 years of age with progressive keratoconus. Materials and Methods. Thirty eyes of 18 patients with established progressive keratoconus underwent preoperative and postoperative visual acuity assessment, topography, and specular microscopy prior to ACXL and were followed up for 24 months. Results. Mean age of the patients was 12.7 years with ten males and eight females. There was an improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 22 publications
3
89
1
Order By: Relevance
“…) and the other applying UVA irradiance at 9 mW/cm 2 over 10 min (Shetty et al. ). Their results were therefore not combined for this review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…) and the other applying UVA irradiance at 9 mW/cm 2 over 10 min (Shetty et al. ). Their results were therefore not combined for this review.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Shetty et al. 18 keratoconic eye were exposed to 10 minutes of UVA light at 9mW/cm2 with a wavelength of 365 nm using the Avedro KXL system (Waltham, MA). Ozgurhan et al.…”
Section: Discussionmentioning
confidence: 99%
“…7 Based on the Bunsen-Roscoe laws of reciprocity, various high-intensity accelerated protocols have emerged to shorten the treatment duration to reduce patient discomfort, while maintaining similar treatment effectiveness as the conventional Dresden protocol. [8][9][10][11][12] Currently, there is still a debate on the effectiveness between conventional CXL and its accelerated counterparts. 13,14 A corneal stromal demarcation line indicating the transition between the anterior cross-linked and posterior untreated corneal stroma could be observed using a slit lamp by as early as 2 weeks after CXL.…”
mentioning
confidence: 99%
“…In one study, in accelerated corneal CXL (9 mW/cm 2 ), a decrease of 2.04 D was detected in K max . On the other hand, in the Siena CXL Pediatrics Trial, the rate of reduction following conventional corneal CXL under protocol was found to be 0.7 D. 22,24 Ulusoy et al found a decrease of 1 D in mean keratometry in pediatric patients. 23 Similarly, variable results (0.06-0.8 D) were obtained in adult groups following accelerated corneal CXL.…”
Section: Discussionmentioning
confidence: 99%